EMPOWERMENT OF THE TEUPING RAYA VILLAGE COMMUNITY, PIDIE REGENCY TO MAKE SALIN NILE FISH (Oreochromis niloticus) SEED FEED WITH SIMPLE MATERIALS: PEMBERDAYAAN MASYARAKAT GAMPONG TEUPING RAYA, KABUPATEN PIDIE UNTUK PEMBUATAN PAKAN BENIH IKAN NILA SALIN (Oreochromis niloticus) DENGAN BAHAN YANG SEDERHANA - Kurnia; Humeira; Ulan Agustina; Zulvia Maika Letis; Ika Rezvani Aprita; Maghfirah (PT. ROCE WISDOM ACEH, 2025)
The purpose of the Community Service (CS) activity is to provide information on making fish feed inGampong Teupin Raya, Batee District, Pidie Regency. This activity was carried out in October 2024 inGampong Teupi Raya, Batee District, Pidie Regency. The method in this CS involves providingmaterials, collecting data, and analysing the results of interviews and observations. The results of thepresentation outline the process of making saline tilapia fish feed (Oreochromis niloticus), specificallygrinding, weighing, mixing, stirring, and then moulding. The moulded material is then dried, and thefinal process involves giving it to saline tilapia fish (Oreochromis niloticus) and storing it.